Warm up with music and visual feedback can effect Wingate performance in futsal players - Bayrakdaroglu, S.; Eken, Ö.; Yagin, F. H.; Bayer, R.; Gulu, M.; Akyildiz, Z.; Nobari, H. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Purpose Visual feedback and music while warm up may help elicit peak performance, but its effect during the Wingate anaerobic test (WAnT) in futsal players is unexplored. Therefore, the aim of this study was to examine the effects of music and visual stimulus on WAnT performance in futsal players.